Measuring and sustaining the new economy : software, growth, and the future of the U.S. economy : report of a symposium - Jorgenson, Dale W. (Dale Weldeau), 1933-; Wessner, Charles W. (National Academies Press, 2006)
Starting in the mid 1990s, the United States economy experienced an unprecedented upsurge in economic productivity. Rapid technological change in communications, computing, and information management continue to promise further gains in productivity, a phenomenon often referred to as the New Economy. To better understand this phenomenon, the National Academies Board on Science, Technology, and Economic Policy (STEP) has convened a series of workshops and commissioned papers on Measuring and Sustaining the New Economy. This major workshop, entitled Software, Growth, and the Future of the U.S. Economy, convened academic experts and industry representatives from leading companies such as Google and General Motors to participate in a high-level discussion of the role of software and its importance to U.S. productivity growth; how software is made and why it is unique; the measurement of software in national and business accounts; the implications of the movement of the U.S. software industry offshore; and related policy issues.